IMPLEMENTASI MODEL PENGUKURAN KINERJA ORGANISASI SEKTOR PUBLIK BERDASARKAN NEW PUBLIC MANAGEMENT: TINJAUAN LITERATURE - Dharmawaty Makur (Program Studi Akuntansi, 2018)
All organizations want a change. Various methods have been used, including in changing the model used to support finance to obtain information for management decisions. This study uses qualitative research methods with data sources based on library research relating to performance appraisal models that have been used specifically in public sector organizations